2022
DOI: 10.3390/vetsci9090484
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Mapping with Indirect Lymphangiography for Canine Mast Cell Tumour

Abstract: Mast cell tumour (MCT) is a common cutaneous and subcutaneous neoplasia in dogs. It can metastasise to lymph nodes (LNs), and this adversely affects the prognosis and treatment. The study aims to evaluate the SLN mapping of MCTs with radiographic indirect lymphography. Dogs that underwent clinical staging were prospectively enrolled. Lipiodol was injected around the MCT or the surgical scar. After 24 h, LNs that picked up contrast were radiographically assessed. Twenty-six dogs with 29 MCTs were included. MCTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 34 publications
3
22
0
Order By: Relevance
“…In agreement with previous studies, 14–16 the results of the current work suggest that the superficial cervical LN is most often the SLN in cMCTs of the pinna, as in approximately 95% of cases the superficial cervical LN was at least one of, if not the only SLN.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In agreement with previous studies, 14–16 the results of the current work suggest that the superficial cervical LN is most often the SLN in cMCTs of the pinna, as in approximately 95% of cases the superficial cervical LN was at least one of, if not the only SLN.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, the superficial cervical LN was never investigated, possibly missing metastatic foci. Our results confirm in a larger population the findings of De Bonis and colleagues, where one out of two dogs with cMCTs of the pinna had SLN metastasis (superficial cervical LN; HN3) 15 …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Most recently, De Bonis et al demonstrated that indirect lymphography using lipidiol and serial radiographs resulted in the detection of at least one SLN in 90% of cases [81]. Their study also described a high discrepancy between RLNs and SLNs, with only 27% full agreement, and interestingly, they also described a considerably lower rate of 50% than other studies utilizing more efficient SLN methods [94].…”
Section: Mast Cell Tumormentioning
confidence: 89%